PERAN MEDIA SOSIAL DALAM MENINGKATKAN DAYA TARIK KAMPUNG WISATA RABUNAN BUMDES BATUR KEC. GADING - Ainul Yaqin Alfaini; Deddy Junaedi (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
This study aims to determine the role of social media in increasing the attractiveness of the Rabunan Tourism Village, managed by the Batur Village-Owned Enterprise (BUMDes), Gading District. The focus of the study includes the use of social media as a means of tourism promotion, its influence on tourist interest, and the obstacles faced by managers in its use. This study uses a qualitative descriptive approach to understand the phenomenon in depth in natural conditions. Data collection techniques were carried out through interviews, observations, and documentation involving the management and related communities. The data obtained were analyzed qualitatively through the processes of data reduction, data presentation, and drawing conclusions. This study is expected to provide an overview of the importance of utilizing social media in village tourism promotion and provide input for the managers of the Rabunan Tourism Village in developing more effective and attractive promotional strategies for the wider community..Keywords : Social Media, Tourist Attractions, Rabunan Tourism Village